The Squash Blossom - Jędrzejko, Paweł (Review of International American Studies, 2019)
Thanks to the unswerving dedication of a small, but enthusiastic group of people, today the Review of International American Studies is indexed in the prestigious Elsevier Scopus database and features in the European Reference Index for the Humanities and Social Sciences (ERIH+); it has its own profile in the Index Copernicus Journal Master List with the Index Copernicus Value (ICV) for 2017 of 77.29 (per 100!). But there is more: recently the RIAS received an “A” class category in the parametric evaluation of the Italian Ministry of Science and was granted as many as 20 parametric points in the most recent evaluation of the Polish Ministry of Science and Higher Education. Our distribution flourishes as well: electronic copies of our journal (both full issues and individual articles) are now available to the readers in hundreds of libraries world-wide via the Central and Eastern European Online Library, an important German content and metadata aggregator run by Wolfgang and Bea Klotz and operating from Frankfurt am Main. Likewise, owing to the steadfast loyalty of Beata Klyta, the indefatigable director of the University of Silesia Press and a major champion of our cause, the RIAS is now available in such renowned repositories as CEJSH, BAZHUM or POLINDEX, which institutions render our texts visible to the reading public world-wide.